(untitled) (Global Journal of Human-Social Science, 2013)
This study aims to deliberate Mimessis which has the most important concept of aesthetics and it s place in the Platon s Philosophy Platon who is the founder of the Forms Theory saw art as Imitation Mimesis and because of this reason he didn t interpret art as Beauty Philosophy s viewpoint he interrepted it into Ideal State What is the cause of this interpretation why should it be censorshiped This article aims to search answers of these questions according to Platon s Forms Theory Beauty Philosophy and art s damage according to Platon